NEW METHODS AND ANALYSES OF COMMUNICATIVE APPROACH IN LEARNING FOREIGN LANGUAGES - Gazieva Shakhnoza (Research Focus International Scientific Journal, 2024)
This article discusses new methods and techniques of the communicative approach in learning foreign languages. It provides information based on analyses of the essence of the communicative approach, the effectiveness of modern methods and techniques in the learning process, and the mobility of an innovative methodological approach in language learning.